Uptake and absorption of fluoranthene from spiked microplastics into the digestive gland tissues of blue mussels, Mytilus edulis L. (September 2021) - Stollberg, Nicole; Kröger, Silja Denise; Reininghaus, Mathias; Forberger, Jens; Witt, Gesine; Brenner, Matthias
Abstract: The present work intended to investigate the fate of contaminant-loaded microplastics if ingested by benthic filter feeder Mytilus edulis under laboratory conditions. In the course of a 7-day experiment the mussels were exposed to PVC microplastics in a size range ≤40 μm, in doses of 2000 particles L −1 (11.56 mg L −1 ). Particles were either virgin or loaded with one of four different nominal concentrations of the polycyclic aromatic hydrocarbon (PAH) fluoranthene (500, 125, 31.25 and 7.8125 μg g −1 ). Verification of fluoranthene concentrations on the particles provided evidence of the high absorptive capacity of PVC for this PAH, indicating that comparable particles may serve as considerable accumulation sites for high concentrations of hydrophobic contaminants in the aquatic environment. Analysis of digestive gland tissues via polarised light microscopy revealed the occurrence of particles and particle aggregates within stomach and intestines of all mussels treated with microplastics, thus making the xenobiotic bioavailable. Results of contaminant analysis in mussel tissues via equilibrium sampling point to a considerable capability of microplastics for the accumulation of hydrophobic contaminants from the environment and their potential to act as vehicles for the transport of theses contaminants into organismal tissues. Graphical abstract: Image 1 Highlights: Internal fluoranthene concentration of mussel tissue determined by equilibrium passive sampling. Proof of contaminant transfer from plastics to organismal tissues. Microplastics identified as source of fluoranthene contamination.